Pengaruh Kompetensi dan Motivasi Terhadap Kinerja Pegawai pada Kantor Bagian Kesejahteraan Rakyat Sekretariat Daerah Kota Makassar - Raodhatuljannah, Andi Sitti; Rusli, Muh (Patria Artha University, 2022)
This research aims to test and analyze the influence of competence on employee performance in the office of the People's Welfare section of the Makassar City Secretariat.Testing and analyzing the influence of motivation on employee performance in the Office of The People's Welfare section of the Makassar City Secretariat. Testing and analyzing the influence of competence and motivation simultaneously on the performance of employees in the Office of The People's Welfare Section of the Makassar City Secretariat.